High-yield and nitrogen self-doped hierarchical porous carbon from polyurethane foam for high-performance supercapacitors. (August 2022) - Zhou, Xiaoli; Zhu, Liyao; Yang, Yue; Xu, Lijie; Qian, Xiujuan; Zhou, Jie; Dong, Weiliang; Jiang, Min
Abstract: Confronted with the environmental pollution and energy crisis issues, upcycling of waste plastics for energy-storage applications has attracted broad interest. Polyurethane (PUR) is a potential candidate for the preparation of N -doped carbon materials. However, its low carbon yield limits the utilization of PUR waste. In this study, PUR foam was converted into N -doped hierarchical porous carbon (NHPC) through an autogenic atmosphere pyrolysis (AAP)-KOH activation approach. An ultra-high carbon yield of 55.0% was achieved through AAP, which is more than 17 times the carbon yield of conventional pyrolysis of PUR. AAP converted 83.2% of C and 61.0% of N in PUR into derived carbon material. The high conversion rate and self-doping effect can increase the environmental and economic benefits of this approach. KOH activation significantly increased the specific surface area of carbon materials to 2057 m 2 g −1 and incorporated hierarchical porous structure and O-containing functional groups to the carbon materials. The obtained NHPCs were applied to improve the performance of supercapacitors. The electrochemical measurement revealed that NHPCs exhibited a high specific capacitance of 342 F g −1 (133 F cm −3 ) at 0.5 A g −1, low resistance, and outstanding cycling stability. The energy density and power density of the supercapacitor were improved to 11.3 W h kg −1 and 250 W kg −1, respectively. This research developed a possible solution to plastic pollution and energy shortage. Graphical abstract: Image 1 Highlights: PUR foam was upcycled into NHPC through AAP and KOH activation. Ultra-high carbon yield (55%) and C conversion rate (83%) were obtained. KOH activation produced a high SSA (2057 m 2 g −1 ) and a hierarchical porosity. NHPC from PUR possessed a remarkable capacitance of 342 F g −1